2003
DOI: 10.1515/reveh.2003.18.2.91
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Combined Metal Interactions in Metal Carcinogenesis: A Review

Abstract: Exposures to complex mixtures of metals in the workplace or environment are more likely to occur than exposures to a single metal alone. The evidence shows that exposures to complex metal mixtures can enhance the risk of cancer in certain human populations. The findings of several studies have suggested, however, that certain metal-metal interactions can inhibit carcinogenic activity. The mechanisms of metalmetal interactions in human carcinogenesis are relatively unknown. Metals represent a highly diverse gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…At the same time, the study of UO 4 bioaccumulation showed that the UO 4 biokinetics in the kidneys, gastrointestinal tract, and excreta, but not in the lungs, were slightly modified by previous UO 2 exposures. All these results show that both genotoxic and biokinetics effects of uranium may depend on preexposure and that repeated exposure induces a potentiation effect compared with acute exposure.Exposures to complex mixtures of metals in the workplace are more likely to occur than exposures to a single compound alone (Madden, 2003). Various forms of uranium (U) are found in the nuclear industry with a variety of isotopic compositions…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the study of UO 4 bioaccumulation showed that the UO 4 biokinetics in the kidneys, gastrointestinal tract, and excreta, but not in the lungs, were slightly modified by previous UO 2 exposures. All these results show that both genotoxic and biokinetics effects of uranium may depend on preexposure and that repeated exposure induces a potentiation effect compared with acute exposure.Exposures to complex mixtures of metals in the workplace are more likely to occur than exposures to a single compound alone (Madden, 2003). Various forms of uranium (U) are found in the nuclear industry with a variety of isotopic compositions…”
mentioning
confidence: 99%
“…Exposures to complex mixtures of metals in the workplace are more likely to occur than exposures to a single compound alone (Madden, 2003). Various forms of uranium (U) are found in the nuclear industry with a variety of isotopic compositions…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposures to complex metal mixtures can enhance the risk of cancer in certain human populations. e �ndings of the review show that combined metal interactions are more important than the sum of the individual metal effects [131]. Combined with mercury or cadmium no observed effect Level (NOEL) dose of lead showed toxicity, indicating that exposure limits may be inefficient in combined exposure situations [132].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Among these proposed mechanisms, oxidative stress is commonly observed in in vivo and in vitro systems during exposure to these metals as mixture [4]. However, several studies suggest that certain metal-metal interactions inhibit carcinogenic activity [14]. Because humans are continually exposed to complex metal mixtures at low doses, it is necessary to determine the mechanism underlying the transformation process.…”
Section: Introductionmentioning
confidence: 99%